The negative effects of conflict to construction industry : a Malaysian perspective / Noraidawati Jaffar ... [et al.] - Jaffar, Noraidawati; Yusof, Ismail; Abdul Tharim, Asniza Hamimi; Ab. Wahid, Abdul Muhaimin; Kurdi, Mohd Khairi; Shuib, Mohammad Nasharudine; Azli, Mohd Syhidi; Ma’arof, Khairul Anuar; Md Salleh, Norazlin (2012)
Conflict is a reality especially in today’s complex construction projects fraught with too many uncertainties. The main goal of this paper is to highlightthenegative effects of conflict in the Malaysian construction industry. Data was obtained by conducting questionnaire surveys among private clients and contractors. Five topmost negative effects of conflict identified were: increasing project costs or claims, project delay, increase in managerial costs, some projects require expensive and time-consuming litigation; and breakdownsin continuing business relationships. This paper hopes to contribute towards a better understanding on the negative effects of conflict, which will result in better conflict management.